Detection of Isotope Stable Radioactive in Soil and Water Marshes of Southern Iraq - Reyam Naji Ajmi (Journal of Global Pharma Technology, 2018)
This study was conducted to indicate Isotopic Stable Radioactive element (ISRe) of the Iraqi marshes by using Geographic Information Systems (GIS) to implement the comparing these elements with World Health Organization elements (WHO), and the Food and Agriculture Organization (FAO), this study achieved in several phases: Work included access to geographical data in six main stations of the Missan governorate (Al- Auda Marsh, Al- Battat Marsh ) during October 2016 period and selection of environmental factors Water and Soil . Results of water in all stations under study showed low concentrations of ISRe Pb212, Pb214,Pb138  and the remaining elements varied and mostly similar limited factors with natural boundaries of water bodies, A little increase come from of some pollutants that are discharged from the water drainage or waste populated .The soil samples showed ISRe, Pb214, Pb212, Pb138 , this may be due to the disintegration of the former previous radioactive element in the same region after wars or explosions , the remaining elements were found in variable concentrations . This database considered as a very important for environmental risks and health in aquatic environmental of marsh which can be updated through a unified future other periodic data. It is one of the method efforts of research for the Iraqi marshes because it represents the concept of ecological zones are covering relatively large areas in southern Iraq, which have a distinctive character of the natural geography of different types so there is a relationship between organisms and their environment an important in an aquatic ecosystem of the food chain.Keywords: Iraqi marsh, Pollution, Bioindicator, Isotopic Stable Radioactive.